Antibiotic use and association with bacterial resistance in a hospital in Southern Brazil (Research, Society and Development, 2020)
Introduction. The increased production of new drugs is parallel with the bacterial adaptation to adverse conditions. There are several factors that have been pointed out as the cause of this, such as: globalization; the abusive use of antibiotics; and the arbitrary prescription of these drugs. Therefore, the objective of the present study was to evaluate antimicrobial usage with antibiotic resistance in 2012 and 2013 at a university hospital in Southern Brazil. Material and Methods. This study was performed at the University Hospital Dr. Miguel Riet Correa Jr. in Rio Grande/RS, Brazil. The data were collected between January 2012 and December 2013, using data from the medical clinic and two intensive care units. Results.  Were observed, 385 and 464 cases of bacterial infections, during the years of 2012 and 2013, respectively. Acinetobacter baumannii, Escherichia coli and Klebsiella pneumoniae were the most prevalent species. The total antibiotic consumption in the University Hospital (HU-FURG) in this period was 3.865 units/dose, with 1.995 units/dose in the year 2012 and 1.870 units/dose in the year 2013. Relationships between the rates of main resistant pathogens isolated and the annual consumption of the corresponding antibiotic (carbapenems, cephalosporins, sulfonamides and other β-lactams) were observed; however, they did not show significant positive associations in increased resistance associated with increased consumption. Conclusion. This study reveals the need for the dissemination and feedback of these data to clinicians and decision-makers at the hospital, as it may be crucial to improve policies on prescribing antibiotics and to implement effective infection control.